2017
DOI: 10.1016/j.clinbiomech.2017.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Passive material properties of stroke-impaired plantarflexor and dorsiflexor muscles

Abstract: Background Following a stroke, intrinsic muscle properties such as stiffness may be altered, which is accompanied by increased spasticity and contractures. Previously, quantification of muscle stiffness has been based off of indirect measurements. Using shear wave ultrasound elastography, direct measurements of muscle material properties can be made. Methods Our aim was to evaluate material properties, specifically passive stiffness, using shear wave ultrasound elastography across a range of muscle lengths, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 47 publications
2
28
0
Order By: Relevance
“…4). This is novel, since the few studies using SWE in stroke subjects were focused on one muscle thought to be representative of the studied muscle group (17,39,44,47,62). Our pictorial analyses highlight that stroke survivors' response is commonly observed at the same muscle regions within plantar flexors: the highest values for GM followed by GL (Fig.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…4). This is novel, since the few studies using SWE in stroke subjects were focused on one muscle thought to be representative of the studied muscle group (17,39,44,47,62). Our pictorial analyses highlight that stroke survivors' response is commonly observed at the same muscle regions within plantar flexors: the highest values for GM followed by GL (Fig.…”
Section: Discussionmentioning
confidence: 81%
“…3B, experiment 2). Of particular relevance, the studies of Mathevon et al (47) and Jakubowski et al (39) focused on GM and reported higher shear modulus on the affected side of stroke survivors. Although we measured the shear modulus during standardized dynamic stretches, these studies positioned the ankle in the targeted angle first, before scanning the GM with the transducer.…”
Section: Discussionmentioning
confidence: 99%
“…For example, previous studies have reported remarkable alterations in muscle architecture in chronic stroke survivors (Li et al 2007;Gao & Zhang, 2008;Gao et al 2009;Zhao et al 2015;Dias et al 2017;. Material properties of muscle and tendon tissues have also been reported to be different in chronic stroke survivors (Zhao et al 2009;Lee et al 2015;Zhao et al 2015;Jakubowski et al 2017). Moreover, contractile properties appear to change in chronic stroke survivors, supported by a narrower width of active force-length curve (Gao & Zhang, 2008) or a greater velocity-dependent concentric torque decay (Clark et al 2006).…”
Section: Limitationsmentioning
confidence: 99%
“…These deficits are attributed to a loss of corticofugal projections that occur post stroke and result in paresis, loss of independent joint control and hypertonicity (Dewald & Beer, 2001;Miller & Dewald, 2012). Associated with neural deficits and resulting disuse, changes in musculoskeletal properties (sarcomere length, fascicle length, stiffness) may also have a negative impact on function, with only a few studies focusing on characterizing these musculoskeletal changes (Jakubowski, Terman, Santana, & Lee, 2017;Landin, Hagenfeldt, Saltin, & Wahren, 1977;Zhao, Ren, Roth, Harvey, & Zhang, 2015). The inability to efficiently and fully activate muscles, combined with decreased use of the upper extremity, will lead to muscle atrophy defined here as a decrease in muscle contractile element volume, and potentially an increase in intramuscular fat.…”
Section: Introductionmentioning
confidence: 99%